Conditions for mental health in education: Towards relational practice. (31st July 2021) - Billington, Tom; Gibson, Sarah; Fogg, Penny; Lahmar, Jamal; Cameron, Harriet
Abstract : There are concerns globally about the emotional wellbeing and mental health of young people and in this paper a critical orientation comprises both theoretical and empirical data sources. The case is made that (1) the medical model of mental health – that of problem identification, diagnosis and medical treatment at the level of the individual – is not appropriate for the vast majority of children and young people in schools and (2) relational approaches would be more sensitive in responding to the complexity of the 'conditions' in the schools, homes and communities in which young people live. Articulations of these conditions in the literature are explored while we also draw on empirical data from part of an evaluation of a school‐based teacher‐training programme in which interviewees and respondents mapped out their own conditions for emotional wellbeing and mental health. We conclude with proposals for relational approaches which (1) acknowledge the links between affect, cognition and school climate and culture, (2) foreground mental health and poverty as impacting on young people's emotional wellbeing in their communities, families and schools and (3) attend to voice – providing spaces in which young people can develop their own 'preferred narratives' concerning emotional wellbeing and mental health.